Determinants of Non Perfomance Financing in Sharia Cooperatives in Indonesia - Jainuri, Ahmad; Orbaningsih, Dwi; Lisa, Oyong (International Journal Labs, 2024)
This study aims to test and analyze: (1) the effect of capital adequacy ratio on non-performance financing, (2) the effect of operating costs on operating income on non-performance financing, (3) the effect of company size on non-performance financing, (4) which among the capital adequacy ratio , Operating costs on operating income and company size, which have a dominant influence on non-performance financing. This research was conducted in sharia cooperatives incorporated in Inkopsyah BMT as many as 30 cooperatives. Samples were determined by saturated sample technique, obtained by 90 such cooperatives during 2020-2022. Data related to research variables were obtained by copying financial statement documents at the cooperative through the http://idx.co.id link. Once the data is collected, it is analyzed by multiple linear regression. Before analysis, tests are first carried out: linearity, feasibility of the model and classical assumptions. To test the hypothesis used t-test. The results of this study prove that: (1) capital adequacy ratio has a significant negative effect on non-performance financing, (2) operating costs on operating income have a significant positive effect on non-performance financing, (3) company size has a significant negative effect on non-performance financing, (4) Operating expenses on operating income have a significant positive dominant effect on non-performance financing.